Structured exercise programs for higher education students experiencing mental health challenges: background, significance, and implementation - Jeftic, Ivan; Furzer, Bonnie J.; Dimmock, James A.; Wright, Kemi; Boyd, Conor; Budden, Timothy; Rosenberg, Michael; Kramer, Ben; Buist, Brett; Fitzpatrick, Ian; Sabiston, Catherine; de Jonge, Melissa; et al. (Frontiers in Public Health, 2023)
The incidence of mental illness is greatest among young adults, and those enrolled in higher education may be particularly vulnerable compared to the general young adult population. Many higher education institutions employ student support staff tasked with implementing strategies to improve student wellbeing and mental illness. However, these strategies tend to be focused on clinical therapies and pharmacological interventions with limited lifestyle approaches. Exercise is an effective method for addressing mental illness and promoting wellbeing, yet widespread provision of structured exercise services to support treatment options for students with mental health challenges has not been fully realized. In an effort to guide exercise strategies for student mental health, we synthesize considerations for developing and delivering exercise programs in higher education settings. We draw directly from the evidence base on existing exercise programs in higher education; and the broader behaviour change, exercise adherence, health psychology, implementation science, and exercise prescription literatures. Our broad considerations cover issues regarding program engagement and behaviour change, exercise ‘dose’ and prescription, integration with other on-campus services, and robust research and evaluation. These considerations may provide impetus for widespread program development and implementation, as well as informing research focused on protecting and improving student mental health.